A comparative field usability study of two lighting measurement protocols. (2018) - Rodriguez, Roberto G.; Monteoliva, Juan Manuel; Pattini, Andrea E.
We developed a lighting measurement protocol (PC-SRT) for Android mobile devices as a replacement of the Argentinean currently mandatory pen-and-paper measurement protocol (SRT-P), and compared their usability in a field study (n = 26) by means of the system usability scale (SUS). Descriptive statistics showed that PC-SRT (SUS = 58.7; SD = 14.9; lower marginally acceptable usability) outscored SRT-P (SUS=47.5; SD=14.5; unacceptable usability). The PC-SRT also performed better in both ease of use and learnability factors. An item-by-item analysis compared the behaviour of each standardised item score; Mann-Whitney test results showed statistically significant differences in SUS-Q1 (U = 36; p = 0.011), SUS-Q2 (U = 35; p = 0.01), SUS-Q4 (U = 46.5; p = 0.05), and SUS-Q7 (U = 39; p = 0.019). These results show that although PC-SRT gathers more data in a wider variety of aspects of the visual environment, users tended to perceive it as easier to use, encouraging the adoption of our proposed lighting measurement protocol for mobile devices.